Parastenopa oglobini (Blanchard) population fluctuation in paraguay tea - Chiaradia, Luís Antonio (2021)
– Larvae of the fly Parastenopa oglobini (Blanchard) (Diptera: Tephritidae) mine the stems of the treesof paraguay tea (Ilex paraguariensis St. Hil., Aqüifoliaceae), and results in swelling, darkening and dropping of theleaves drying of the sprouts and reduction of the orchard productivity. With the objective to assess the populationfluctuation of adults of this insect, a study was conducted in an orchard situated in Chapecó, Santa Catarina, Brazil.The samplings were carried out in the period of July of 2003 to June of 2006 using vacuum equipment (D-Vac).Fly incidence was low in the late Winter and beginning of Spring and higher in the months with high temperatures.Average temperature and wind speed had the greatest influences on the population of this pest.